Detecting carbapenemase-producing Enterobacterales (CPE): an evaluation of an enhanced CPE infection control and screening programme in acute care. (1st June 2020) - Otter, Jonathan A; Mookerjee, Siddharth; Davies, Frances; Bolt, Frances; Dyakova, Eleonora; Shersing, Yeeshika; Boonyasiri, Adhiratha; Weiße, Andrea Y; Gilchrist, Mark; Galletly, Tracey J; Brannigan, Eimear T; Holmes, Alison H
Abstract: Objectives: The transmission of carbapenemase-producing Enterobacterales (CPE) poses an increasing healthcare challenge. A range of infection prevention activities, including screening and contact precautions, are recommended by international and national guidelines. We evaluated the introduction of an enhanced screening programme in a multisite London hospital group. Methods: In June 2015, an enhanced CPE policy was launched in response to a local rise in CPE detection. This increased infection prevention measures beyond the national recommendations, with enhanced admission screening, contact tracing and environmental disinfection, improved laboratory protocols and staff/patient education. We report the CPE incidence and trends of CPE in screening and clinical cultures and the adoption of enhanced CPE screening. All non-duplicate CPE isolates identified between April 2014 and March 2018 were included. Results: The number of CPE screens increased progressively, from 4530 in July 2015 to 10 589 in March 2018. CPE detection increased from 18 patients in July 2015 (1.0 per 1000 admissions) to 50 patients in March 2018 (2.7 per 1000 admissions). The proportion of CPE-positive screening cultures remained at approximately 0.4% throughout, suggesting that whilst the CPE carriage rate was unchanged, carrier identification increased. Also, 123 patients were identified through positive CPE clinical cultures over the study period; there was no significant change in the rate of CPE from clinical cultures per 1000 admissions ( P = 0.07). Conclusions: Our findings suggest that whilst the enhanced screening programme identified a previously undetected reservoir of CPE colonization in our patient population, the rate of detection of CPE in clinical cultures did not increase.